Can agronomic phosphorus recommendations for potato be environmentally sustainable? - Zamuner, Ester Cristina (2017)
A better understanding of the relationship between the agronomic and environmental optimum for soil test P can guide potato growers in Buenos Aires province towards improved P fertilizer management.